A comparative study on the fasting and postprandial lipid abnormalities in type 2 diabetes mellitus in tertiary care teaching hospital of southern Rajasthan, India - Nadeem, Sharique; Singh, Lakhan; Shukla, Uma Shankar; Jain, Mayank; Kumar, Vinod (International Journal Of Community Medicine And Public Health, 2022)
Background: The worldwide prevalence of diabetes mellitus has risen dramatically. Based on current trends, the International Diabetes Federation projects that 438 million individuals will have diabetes by the year 2030.Type 2 diabetes is characterized by insulin resistance which is associated with hypertension, dyslipidemia, micro and macro vascular disease. Methods: This study was institutional based Case Control comparative study carried out on 200 type 2 diabetes patients and on 200 healthy controls at tertiary care teaching hospital in Jhalawar, Rajasthan. Non-probability purposive sampling technique was used followed by interview of 400 participants. Results: In final analysis, Diabetes subjects were middle aged (mean age 43.2±7.48 years) with a mean BMI of 26.9±5.46 kg/m2, matched with controls. Among diabetes patients 152 has positive family history for diabetes. The fasting and postprandial lipid profile were increased in the type 2 DM subjects as compared to controls and among the type 2 DM patients, the postprandial lipid parameters were increased as compared to the fasting level. Conclusions: Both fasting and post prandial lipid abnormalities seen in type 2 diabetes but the post- prandial lipid profile was altered when compare to fasting lipid levels. Lifestyle modifications along with diet and proper lipid lowering drugs are helpful in diabetic individuals with lipid abnormalities.